SOCIALIZATION OF THE CAPITAL MARKET USING SMART ONLINE TRADING METHODS WITH BIONS - Fitri, Aida; Sartika, Fani; Saputra, Aiyup (Universitas Muhammadiyah Aceh, 2022)
The purpose of this community service is to provide knowledge about Smart Trading with BIONS, in Banda Aceh. The outputs obtained from this community service activity include: (1) participants were given the knowledge about buying shares using the Online Trading Method with BIONS, (2) from the results obtained that the participants understood about the contents of the materials and at the end of the session were given question and time to answer, a number of questions obtained form participants and the public including; (a) How to register and join in Sharers, (b) How to buy and sell shares, and (c) How to decide which stocks are good to buy. Keywords: Stock trading, BIONS